Retrospective Cohort Study on Potential Risk Factors for Repeated Need of Dental Rehabilitation under General Anesthesia in a Private Pediatric Dental Practice - Viktoria Karl; Konstantin Johannes Scholz; Karl-Anton Hiller; Isabelle Tabenski; Frederike Schenke; Wolfgang Buchalla; Christian Kirschneck; Katrin Bekes; Fabian Cieplik (MDPI AG, 2022)
The need for dental rehabilitations under general anesthesia (DRGAs) is continuously increasing, particularly for dental treatment of children. The present retrospective cohort study aimed to investigate potential risk factors for repeated need of DRGA in a cohort of patients from a private pediatric dental practice. Demographic and anamnestic data, dental status, and treatments performed during DRGA were retrospectively analyzed from the electronic dental charts of 1155 children that received at least one DRGA between October 2016 and December 2021. The median age of all children was 5 years at time of their first DRGA. The rate of repeated DRGAs was 9%. Patients with repeated need of DRGA were significantly younger at time of their first DRGA and revealed significantly more often a history of preterm birth and current use of a baby bottle as compared to patients with only one DRGA. There were significantly fewer treatments (regardless of type) in the second DRGA than at the first. Within the limitations of this study, young age at first DRGA, a history of preterm birth, and current use of a baby bottle may be risk factors for repeated need of DRGA. The search for effective strategies to minimize the repeated need for DRGA in children remains critical.